BETWEEN MYTHS AND ETHOS: FRAMING MESSAGES FOR ENVIRONMENTAL COMMUNICATION OF KAMPUNG NAGA TASIKMALAYA WEST JAVA - Suwandi Sumartias; Priyo Subekti; Susie Perbawasari; Iriana Bakti (Universitas Padjadjaran, 2022)
Kampung Naga, also called Naga Village, is a customary community that still preserves the traditions of their ancestors, which in this case is the Sundanese culture. They live adjacent to nature, believe that it is a gift from God, and based on this concept, they consider natural disasters as causes of bad human behavior. This belief exists because the village does not only live in nature but with it as well, and as a customary community, they have their ways of managing it. Therefore, this research aims to determine the myths and ethos associated with environmental communication activities. It also tries to identify the role of traditional leaders in transmitting cultural values to the younger generation through these activities. The results showed that the Naga Village community uses myths and ethos for environmental communication through the Pamali concept and by living with nature. They are also good role models in inheriting values, which become tools to awaken the community and the young generation, and these are often conveyed at traditional events as manifestations of their beliefs in nature. The inheritance of values by the younger generation is performed through the enculturation process to develop customs that will later become social controls in the community.